PENGARUH KERAPATAN NAUNGAN TERHADAP KUALITAS BIJI KOPI ARABIKA (Coffea arabika L.) - Sukanto, Sukanto; Saputra, Whin Themas Mico; Purnama, Rizskywan; Syahputra, Syahdan (Universitas Gajah Putih, 2023)
This research aims to determine the influence of the quality of Arabica coffee beans and to determine the influence of interactions between these two factors. This research was carried out on farmers' plantations in Bener Meriah Regency which corresponds to the level of research that has been carried out. The parameters observed consisted of the weight of 1000 red fruits, the percentage of normal seeds, triangular seeds, elephant seeds, round seeds, yield and green traces. The results of the research showed that the influence of altitude and density of lamtoro naugan had a very significant effect on the weight of 1000 red fruits, triangular seeds and green beans and was significantly different for normal seeds, round seeds and yield. There was no real interaction Naugan Density in each observation.